2015
DOI: 10.1007/s11031-015-9470-5
|View full text |Cite
|
Sign up to set email alerts
|

Motivational systems and autonomic functioning: Overlapping and differential contributions to anhedonic depression and anxious arousal

Abstract: This study examined multiple aspects of temperament in order to better understand the distinction and overlap between anxious and depressive symptoms in emerging adulthood. Temperament was measured at the motivational level via self-reported behavioral inhibition (BI) and behavioral activation (BA) and at the physiological level via autonomic functioning [i.e., skin conductance levels (SCL) and respiratory sinus arrhythmia (RSA)]. Emerging adults (N = 170) reported on their BI and BA; SCL and RSA baseline scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…In a longitudinal study in adolescents, Vazquez and colleagues (2016) found a significant, prospective association between resting HRV and anhedonia, but not negative mood or interpersonal problem symptoms of depression assessed one year later. Further, Sanders and Abaied (2015) found a significant relationship between low HRV and greater anhedonic depression, but not anxious arousal symptoms. Interestingly, in two recent studies high HRV demonstrated specific associations with manic symptoms, suggesting that HRV may generally index disturbances in positive valence and reward processing neural systems (Faurholt-Jepsen, Brage, Kessing, & Munkholm, 2017; Gruber, Mennin, Fields, Purcell, & Murray, 2015).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In a longitudinal study in adolescents, Vazquez and colleagues (2016) found a significant, prospective association between resting HRV and anhedonia, but not negative mood or interpersonal problem symptoms of depression assessed one year later. Further, Sanders and Abaied (2015) found a significant relationship between low HRV and greater anhedonic depression, but not anxious arousal symptoms. Interestingly, in two recent studies high HRV demonstrated specific associations with manic symptoms, suggesting that HRV may generally index disturbances in positive valence and reward processing neural systems (Faurholt-Jepsen, Brage, Kessing, & Munkholm, 2017; Gruber, Mennin, Fields, Purcell, & Murray, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…More pertinently, two recent studies suggest that low HRV might be specific to anhedonia compared to other symptoms of depression and anxious arousal (Sanders & Abaied, 2015; Vazquez et al, 2016). Thus, given data that suggests pupil dilation in response to reward cues reflects reward processing (Graham et al, 2011; Kennerley & Wallis, 2009; O’Doherty, Buchanan, Seymour, & Dolan, 2006; O’Doherty, Dayan, Friston, Critchley, & Dolan, 2003; Sepeta et al, 2012; Steinhauer & Hakerem, 1992), decreased pupil dilation while viewing positive emotional stimuli might be associated with low HRV.…”
Section: Introductionmentioning
confidence: 99%